Development of high power microwave compressors; Instruments and Experimental Techniques; № 3 - Novikov S. A. Sergey Avtonomovich; Yushkov Y. G. Yuri Georgievich; Artemenko S. N. Sergey Nikolaevihc; Chumerin P. Yu.; Shpuntov R. V. (2004, 2004)
В фонде НТБ ТПУ отсутствует